Madison's Metronome : The Constitution, Majority Rule, and the Tempo of American Politics. - Weiner, Greg (University Press of Kansas, 2022)
Examines the significance of time in James Madison's theory of majority rule. Madison worried that the drive for instant political gratification might lead to an inflamed majority that would not rule reasonably. His philosophy-that the natural power of time will defuse passions-is incompatible with the current political ethos that values quick decision-making.
Description based upon print version of record.
Keywords: Madison, James, -- 1751-1836 -- Political and social views.; Majorities.; Republicanism -- United States -- History -- 18th century.; Federal government -- United States -- History -- 18th century.; United States -- Politics and government -- Philosophy.; Majorité (Droit constitutionnel); Républicanisme -- États-Unis -- Histoire -- 18e siècle.; États-Unis -- Politique et gouvernement -- Philosophie.; Revolutionary Period (1775-1800); United States.; HISTORY.; Political.; PHILOSOPHY.; Political Process.; POLITICAL SCIENCE.; Constitutions.; Electronic books.